Unwinding of synthetic replication and recombination substrates by Srs2 - Marini, Victoria; Krejci, Lumir (DNA repair, 2012)
The budding yeast Srs2 protein possesses 3' to 5' DNA helicase activity and channels untimely recombination to post-replication repair by removing Rad51 from ssDNA. However, it also promotes recombination via a synthesis-dependent strand-annealing pathway (SDSA). Furthermore, at the replication fork, Srs2 is required for fork progression and prevents the instability of trinucleotide repeats. To better understand the multiple roles of the Srs2 helicase during these processes, we analysed the ability of Srs2 to bind and unwind various DNA substrates that mimic structures present during DNA replication and recombination. While leading or lagging strands were efficiently unwound, the presence of ssDNA binding protein RPA presented an obstacle for Srs2 translocation. We also tested the preferred directionality of unwinding of various substrates and studied the effect of Rad51 and Mre11 proteins on Srs2 helicase activity. These biochemical results help us understand the possible role of Srs2 in the processing of stalled or blocked replication forks as a part of post-replication repair as well as homologous recombination (HR).
Keywords: Rad51 Recombinase; DNA Helicases; homologní rekombinace; Replication Protein A; Saccharomyces cerevisiae - proteiny; rekombinasa Rad51; DNA, Single-Stranded; endodeoxyribonukleasy; Homologous Recombination; DNA-helikasy; jednovláknová DNA; Saccharomyces cerevisiae Proteins; DNA Replication; delece genu; replikační protein A; Endodeoxyribonucleases; Gene Deletion; exodeoxyribonukleasy; replikace DNA; Saccharomyces cerevisiae; křížová struktura DNA; Exodeoxyribonucleases; DNA, Cruciform